2018
DOI: 10.3906/sag-1804-57
|View full text |Cite
|
Sign up to set email alerts
|

Multitarget therapy versus intravenous cyclophosphamide in the induction treatment of lupus nephritis: a metaanalysis of randomized controlled trials

Abstract: Background/aim: Multitarget therapy for lupus nephritis (LN) remains in its exploratory phrase and the recent evidence is insufficient. This study aimed to evaluate the efficacy and safety of mycophenolate mofetil (MMF), tacrolimus (TAC), and steroids (multitarget therapy) versus intravenous cyclophosphamide (IVC) and steroids in induction treatment of LN. Materials and methods: We searched for randomized controlled trials of MMF plus TAC versus IVC in LN using PubMed, EMBASE, the Cochrane Central Register of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Furthermore, the adverse effects of multitarget therapy consisting of a triple immunosuppressant combination, though effective at inducing remission, should be particularly considered given that adding pharmacotherapies may negatively impact quality of life. Multitarget therapy is most effective in class IV and class V LN lesions, and it has been reported that higher proportions of patients find the adverse effects of multitarget therapy intolerable compared to CPA and GC [19]. Multidrug therapy does not increase rates of infection or malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the adverse effects of multitarget therapy consisting of a triple immunosuppressant combination, though effective at inducing remission, should be particularly considered given that adding pharmacotherapies may negatively impact quality of life. Multitarget therapy is most effective in class IV and class V LN lesions, and it has been reported that higher proportions of patients find the adverse effects of multitarget therapy intolerable compared to CPA and GC [19]. Multidrug therapy does not increase rates of infection or malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…In two studies by Deng et al and Tunnicliffe et al, a combination of MMF, TAC, and GC ("multitarget therapy") increased complete remission rates over CPA and GC alone (RR 2.38; 95% CI: 1.07-5.30) [5,19]. Zhou et al, however, did not find differences in complete remission rates between these interventions (RR 5.13; 95% CI: 0.75-35.02), but in all three meta-analyses, the largest individual study effect size showed improved outcomes with multitarget therapy [5,11,19]. Furthermore, TAC improved complete remission rates when compared individually against other agents (RR 1.48; 95% CI: 1.23-1.77) and compositely with GC against CPA and GC (RR 2.41; 95% CI: 1.8-3.99) [10,20].…”
Section: Complete and Partial Remission Rates During Induction Therap...mentioning
confidence: 99%
“…In fact, combination therapy with a steroid, TAc and MMF has achieved a good therapeutic effect in clinical practice in LN. Previous studies have found that the combination of TAc and MMF is more effective and safer than conventional treatment (intravenous cyclophosphamide and steroid) (9,10,21,22). Some studies have reported that TAc combined with MMF treatment may be a beneficial option for patients with LN who exhibit an inadequate response to either cyclophosphamide or MMF treatment, or had lupus flares after achieving a complete response (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians need to carefully consider the choice of immunosuppressants its dose and its drug combinations. Pathological morphology and occurrence mechanism are the most important references for drug use [ 55 ]. High doses of hormone (oral prednisone 1 mg/kg) primarily block the effects of NF- κ B and inhibit various inflammatory factors.…”
Section: Clinical Use Of Cy In Induction Remission In Lnmentioning
confidence: 99%